Overproduction of IL-6 and Type-I IFN in a Lethal Case of Chikungunya Virus Infection in an Elderly Man During the 2017 Italian Outbreak. (25th October 2018) - Colavita, Francesca; Vita, Serena; Lalle, Eleonora; Carletti, Fabrizio; Bordi, Licia; Vincenti, Donatella; Pozzetto, Irene; Aiuti, Massimo; Vairo, Francesco; Capobianchi, Maria Rosaria; Lichtner, Miriam; Castilletti, Concetta
Abstract: Chikungunya fever is caused by Chikungunya virus (CHIKV) and is generally considered a self-limiting disease. However, severe clinical presentations with a high mortality rate have been reported in association with underlying medical conditions. This study reports the molecular characterization of the virus and an abnormal pattern of circulating cytokines in a unique lethal CHIKV case during the 2017 outbreak in Italy, which involved an elderly patient with underlying cardiac disease. Analysis of inflammatory cytokines revealed a strong increase of interferon (IFN)-α and IFN-β, as well as interleukin-6, suggesting a possible role of type-I IFN in the cytokine storm, which may be correlated with unfavorable prognosis of CHIKV infection.